Reducing Social Isolation Amongst Older People - Implications for Health Professionals - Howat, Peter; Iredell, H.; Grenade, Linda; Nedwetzky, Anita; Collins, Jennifer (Geriaction Incorporated, 2004)
Social isolation is a significant factor effecting the health status of the ageing Australian population. Social isolation can be partly remedied by strategies that encourage social participation. However, there is scant evidence ofrigorous and appropriate evaluation of programs incorporating social participation strategies.